Moral Expertise and the Credentials Problem - Cholbi, Michael (Ethical theory and moral practice, 2007)
Philosophers have harbored doubts about the possibility of moral expertise since Plato. I argue that irrespective of whether moral experts exist, identifying who those experts are is insurmountable because of the credentials problem: Moral experts have no need to seek out others’ moral expertise, but moral non-experts lack sufficient knowledge to determine whether the advice provided by a putative moral expert in response to complex moral situations is correct and hence whether an individual is a bone fide expert. Traditional accounts of moral expertise require that moral experts give reliably correct moral advice supported by adequate justification, an account which, I argue, is too lean in allowing for the possibility of a moral expert who is motivationally indifferent to her own moral judgments and advice. Yet even if the proposition that a moral expert is an individual who provides reliably correct moral advice supported by adequate justification and is necessarily motivated by that advice exhausts the necessary and sufficient conditions for moral expertise, this proposition cannot function as an applicable criterion for non-experts to use in appraising would-be experts’ claims to expertise. The credentials problem thus remains unanswered.